2016
DOI: 10.1089/scd.2015.0367
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Supports Osteogenic Lineage Decisions in Embryonic Stem Cells

Abstract: The specification of pluripotent stem cells into the bone-forming osteoblasts has been explored in a number of studies. However, the current body of literature has yet to adequately address the role of Wnt glycoproteins in the differentiation of pluripotent stem cells along the osteogenic lineage. During mouse embryonic stem cell (ESC) in vitro osteogenesis, the noncanonical WNT5a is expressed early on. Cells either sorted by their positive WNT5a expression or when supplemented with recombinant WNT5a (rWNT5a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…wnt 5a to limit IVD inflammation by inhibiting the action of TNFα. Nevertheless, in vivo application does require caution, as multiple reports have presented the ability of wnt5a to induce or support osteogenesis, [78][79][80] tissue-fibrosus, 81,82 and M2 polarization of macrophages. 83 Similarly, wnt3a has been associated with the progression of a variety of tumors.…”
Section: Wnt3a and Wnt5a As Tools For Regeneration Of The Intervertebmentioning
confidence: 99%
“…wnt 5a to limit IVD inflammation by inhibiting the action of TNFα. Nevertheless, in vivo application does require caution, as multiple reports have presented the ability of wnt5a to induce or support osteogenesis, [78][79][80] tissue-fibrosus, 81,82 and M2 polarization of macrophages. 83 Similarly, wnt3a has been associated with the progression of a variety of tumors.…”
Section: Wnt3a and Wnt5a As Tools For Regeneration Of The Intervertebmentioning
confidence: 99%
“…It also regulates the expression of MESP1 and cardiomyocyte differentiation via non-Wnt/β-catenin signaling [38]. Wnt-5a is expressed at an early of in vitro osteogenesis differentiation [39]. Together, these experiments show that Wnt-5a can activate multiple receptors to influence various cellular processes during embryonic development.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have found that the canonical WNT3A and the non-canonical WNT5A have the effect of promoting bone formation in collaboration with each other. If Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry rWNT3A was supplemented during a time window following rWNT5A treatment, osteogenic differentiation was enhanced both in murine and human ESCs [39]. Sphingosine-1-phosphate (S1P) -enhanced Wnt5a promotes low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6) expression, resulting in the trigger of osteogenic differentiation of C3H10T1/2 cells [40].…”
Section: Discussionmentioning
confidence: 99%